Inventory management system and financial performance analysis of Shabab Fabrics Limited - Akter, Mahabuba (BRAC Business School (BBS), BRAC University, 2013)
This report is done based on my three month internship program that I have completed at Shabab Fabrics Limited, Head of Corporate Branch from October 2012 to January 2013 as an partial requirement to complete my bachelor degree from BRAC University. The topic of my internship report is- “The Inventory Management System and financial performance evaluation of Shabab Fabrics Limited.” Shabab Fabrics is one of the well known towel manufacturing company in Bangladesh. It is producing the quality towel products and distributed all over our country. Shabab Fabrics is renown in international market to export terry towel products. Like other manufacturing companies SFL also collect raw materials from own premise and abroad. Therefore, inventory purchase and management system is one of the significant issues for SFL. To produce their products they need more than 100 direct and indirect materials. To purchase their inventory they do some of the tasks in orderly like prepare budget, prepare purchase order then negotiated with supplier and finally purchase Raw materials. Then to proper manage of this inventory they also need to do some tasks like received raw materials, issue raw materials, finished goods received, finished goods disburse, reconciliation of raw materials and then if any sales return have. By monitoring this system, they can get proper value of inventory, though some other issues may need to consider. SFL and its group company FMYDL and their sister concern CREA use common warehouse for storage their inventory. Therefore, SFL cannot differentiate their warehouse cost; carrying costs, which mislead SFL cost of goods sold and gross profit value. They have more than 100 categories of raw materials and for every single category, they need to calculate lead-time individually and maintain safety stock, which also create obstacle for proper inventory management. Moreover, lack of proper planning and coordination and Troyee software limitation they are not able to get the accurate value of inventory and cost of goods sold. Therefore, it will be more beneficiaries for SFL if they can identify their warehouse cost separately and allocate them properly. Another most important issue for SFL is performance analysis of in every year and takes decision for improvement. To do so ratio calculation and analysis is one of the key mechanisms. To clear about SFL financial position calculated current ratio, Net working capital, Return on Assets, Return on Equity, Profit Margin, Gross profit Margin, Assets Turnover Ratio, Account Receivable Turnover Ratio, Inventory Turnover, and Debt to Equity, Debt Ratio and Fixed Assets Turnover Ratio. To analyze these ratio values we can get the idea of financial performance and give recommendation about it.